A Framework for Modeling Local Production Systems with Techno‐Ecological Interactions. (22nd August 2016) - Martinez‐Hernandez, Elias; Leung Pah Hang, Melissa Yuling; Leach, Matthew; Yang, Aidong
Summary: At the local scale, interconnected production, consumption, waste management, and other man‐made technological components interact with local ecosystem components to form a local production system. The purpose of this work is to develop a framework for the conceptual characterization and mathematical modeling of a local production system to support the assessment of process and component options that potentially create symbiosis between industry and ecosystem. This framework has been applied to a case study to assess options for the establishment of a local energy production system that involves a heathland ecosystem, bioenergy production, and wastewater treatment. We found that the framework is useful to analyze the two‐way interactions between these components in order to obtain insight into the behavior and performance of the bioenergy production system. In particular, the framework enables exploring the levels of the ecosystem states that allow continuous provisioning of resources in order to establish a sustainable techno‐ecological system.